2020
DOI: 10.1111/ijcp.13586
|View full text |Cite
|
Sign up to set email alerts
|

Early biomarkers of diabetic kidney disease. A focus on albuminuria and a new combination of antidiabetic agents

Abstract: Aims We aimed to determine the efficacy and safety of sodium‐glucose cotransporter type 2 inhibitors (SGLT2i) and glucagon‐like peptide‐1 receptor agonists to prevent worsening urinary albumin‐to‐creatinine ratio as an early biomarker of diabetes kidney disease. Methods A total of 178 patients with type 2 diabetes and obesity received combination treatment with SGLT2i added to GLP1ra (n = 76), GLP1ra added to SGLT2i (n = 50) or GLP1ra plus SGLT2i from start (n = 52), according to investigators´ best clinical j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…UACR did not decrease significantly in any of the groups, probably because of the small number of participants per group. Two previous studies have found similar reductions in UACR compared with baseline for the combination treatment [39,40]. Furthermore, the small reduction in UACR in the empagliflozin group might be attributed to the low baseline values (Table 1) and, as changes in oxygenation may precede changes in UACR, we were not able to fully establish the link between the two.…”
Section: Discussionmentioning
confidence: 59%
“…UACR did not decrease significantly in any of the groups, probably because of the small number of participants per group. Two previous studies have found similar reductions in UACR compared with baseline for the combination treatment [39,40]. Furthermore, the small reduction in UACR in the empagliflozin group might be attributed to the low baseline values (Table 1) and, as changes in oxygenation may precede changes in UACR, we were not able to fully establish the link between the two.…”
Section: Discussionmentioning
confidence: 59%
“…In the study by Carretero-Gomez et al [ 28 ], the extent of reduction in the total UACR was significant and similar when the combination was started simultaneously or when a GLP-1RA was added to ongoing SGLT2i therapy (− 17.19 mg/g and − 16.4 mg/g, respectively; p < 0.0001). A greater reduction in macroalbuminuria was observed when an SGLT2i was added to a GLP-1RA than when a GLP-1RA was added to an SGLT2i (− 116.7 mg/g [n = 24] and − 55.5 mg/g [n = 21]; p < 0.005).…”
Section: Resultsmentioning
confidence: 87%
“…3 E). Two studies (Carretero-Gomez et al [ 28 ] and Diaz-Trastoy et al [ 26 ]) reported results related to albuminuria. In the study by Carretero-Gomez et al [ 28 ], there was a significant reduction in total urinary albumin-to–creatinine ratio (UACR; − 15.14 mg/g; p < 0.0001) and macroalbuminuria (UACR > 30 mg/g; − 63.18 mg/g; p < 0.0001) at 26 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A post hoc analysis in the CREDENCE trial showed a greater relative reduction in UACR in patients with lower baseline albuminuria levels [29] . Combined treatment of GLP-1RA and SGLT2i has beneficial effects on UACR [30] . In patients with type 1 diabetes and a baseline UACR ≥ 30 mg/g, solagliflozin was able to reduce UACR [31] .…”
Section: Discussionmentioning
confidence: 99%